(untitled) (Ascendens Asia Singapore – Bestlink College of the Philippines Journal of Multidisciplinary Research, 2019)
Office procedure plays an important role in the success of a certain business. However, the effectiveness of every procedure becomes the issue. This development study focuses on the office procedure of the Laboratory Department and Finance and Audit Department in ABC Company. The researchers explore the existing problems that the employees encounter on a daily basis and provide possible solution to the problems that may enhance the current work flows of the selected department. Qualitative method was used in this study to gain an understanding of the current situation of the selected departments. The proponents used observation, interviews and survey questionnaires to obtain information from the employees of the two departments. An ocular visit was performed to see the actual work flow. An interview was also conducted to selected employees to determine their personal experiences and insights with regards to the work problems they encounter on a daily basis. Furthermore, survey questionnaires were provided to identify the existing problems that happen inside their respective departments. Based on the findings, the main problem in the two departments is lack of manpower. The researchers observed that this problem may cause unproductivity once one employee is absent. The absences of the staff greatly affect the production of work in each department. In an interview with the department head, the researchers found out that there are some deficiencies in payment process the need to be enhanced in the current situation, the payment procedure composed of two process: payment through cash, payment through bank. The growing demand of customer who want to pay over-the-counter lead to overload work to the employees of finance and audit department. This result to delay of work and transaction. Based on the findings, majority of the respondents agreed that the main problem was lack of manpower. These findings display the need for additional of at least two employees in Finance and Audit Department. The researchers also recommend adding online payment process to help the staff to lessen the work. Furthermore, realigning some work procedure can minimize the time of work.